Transportation Management: A Study of Consumer Durables in India - Soi, Kamal (Gyan Management Journal, 2010)
Logistics costs, that is, transportation, inventory holding, warehousing, packaging, losses and re;;:s administration costs have been estimated at 13-14% of Indian GDP which is higher than 8% of USA’s & 6-B=.: r, other developed countries. Out of this %age of logistics cost, transportation contributes more than 40 % an; , . transit losses 14%, thus, both put together account for more than half the logistics cost. Present empirical s-:.1:, is an attempt to get insight into the problems & critical role of transportation management with sp.reference to in-transit losses in the consumer durables sector in India. Top consumer durable companies Videocon & Onida have been undertaken for the study. The study is based on the primary informatio